2024
DOI: 10.3390/ijms25052797
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transglutaminase 2 in Cancer: An Update

Elisabetta Zaltron,
Federica Vianello,
Alessia Ruzza
et al.

Abstract: Transglutaminase type 2 (TG2) is the most ubiquitously expressed and well characterized member of the transglutaminase family. It is a ubiquitous multifunctional enzyme implicated in the regulation of several cellular pathways that support the survival, death, and general homeostasis of eukaryotic cells. Due to its multiple localizations both inside and outside the cell, TG2 participates in the regulation of many crucial intracellular signaling cascades in a tissue- and cell-specific manner, making this enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 151 publications
(241 reference statements)
0
1
0
Order By: Relevance
“…Specific MMP ELISA assays for MMP2, MMP9, and MMP14 revealed that cysteamine specifically decreased levels of these MMPs, indicating that the molecular mechanism of cysteamine treatment is dependent on the activity of MMP2, MMP9, and MMP14 ( Figure 3 C–E). Transglutaminase 2 (TGM2) plays a crucial role in the epithelial–mesenchymal transition and TRAIL resistance; its increased level contributes invasion and migration in cancer cells [ 15 ]. We found that mRNA expression levels of TGM2 and MMP2/MMP9/MMP14 were positively correlated in the TCGA GBM patient database, suggesting that TGM2 may be involved in MMP pathways in GBM ( Figure 3 F).…”
Section: Resultsmentioning
confidence: 99%
“…Specific MMP ELISA assays for MMP2, MMP9, and MMP14 revealed that cysteamine specifically decreased levels of these MMPs, indicating that the molecular mechanism of cysteamine treatment is dependent on the activity of MMP2, MMP9, and MMP14 ( Figure 3 C–E). Transglutaminase 2 (TGM2) plays a crucial role in the epithelial–mesenchymal transition and TRAIL resistance; its increased level contributes invasion and migration in cancer cells [ 15 ]. We found that mRNA expression levels of TGM2 and MMP2/MMP9/MMP14 were positively correlated in the TCGA GBM patient database, suggesting that TGM2 may be involved in MMP pathways in GBM ( Figure 3 F).…”
Section: Resultsmentioning
confidence: 99%